2016
DOI: 10.18632/oncotarget.11999
|View full text |Cite
|
Sign up to set email alerts
|

Identification of long non-coding RNAs biomarkers for early diagnosis of myocardial infarction from the dysregulated coding-non-coding co-expression network

Abstract: Long non-coding RNAs (lncRNAs) have recently been shown as novel promising diagnostic or prognostic biomarkers for various cancers. However, lncRNA expression patterns and their predictive value in early diagnosis of myocardial infarction (MI) have not been systematically investigated. In our study, we performed a comprehensive analysis of lncRNA expression profiles in MI and found altered lncRNA expression pattern in MI compared to healthy samples. We then constructed a lncRNA-mRNA dysregulation network (DLMC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…Moreover, they have been shown to serve as molecular scaffolds for nuclear compartmentalization, recruiters for chromatin‐modifying complexes, miRNA sponges and gene controllers for sequestration . Considering that lncRNAs play a diverse role in cellular networks, they have been implicated as contributing factors to many human disorders, such as cancers, neurological disorders, and CVD . It has been shown that aberrant lncRNAs expression can result in dysregulation of downstream effector molecules and consequently lead to the pathogenesis of CVD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, they have been shown to serve as molecular scaffolds for nuclear compartmentalization, recruiters for chromatin‐modifying complexes, miRNA sponges and gene controllers for sequestration . Considering that lncRNAs play a diverse role in cellular networks, they have been implicated as contributing factors to many human disorders, such as cancers, neurological disorders, and CVD . It has been shown that aberrant lncRNAs expression can result in dysregulation of downstream effector molecules and consequently lead to the pathogenesis of CVD.…”
Section: Introductionmentioning
confidence: 99%
“…8 Considering that lncRNAs play a diverse role in cellular networks, they have been implicated as contributing factors to many human disorders, such as cancers, neurological disorders, and CVD. [9][10][11] It has been shown that aberrant lncRNAs expression can result in dysregulation of downstream effector molecules and consequently lead to the pathogenesis of CVD. Recent studies also showed that lncRNAs were pivotal regulators of VSMCs and ECs proliferation, migration, and cell motility.…”
Section: Introductionmentioning
confidence: 99%
“…24 In a study on myocardial infarction and lncRNA expression profiles, the functional analysis demonstrated that a total of 9 lncRNAs were involved in myocardial innate immune responses, and the dysregulation of these lncRNAs led to abnormalities of the immune system. 25 Knowledge on the regulatory effects of lncRNAs on AMD progression, and the detailed functions of lncRNAs on the incidence of early AMD, is quite limited. In a previous study, the detection of dysregulated lncRNAs in pathological neovascularization provided evidences of late AMD development.…”
mentioning
confidence: 99%
“…Recently, some studies have suggested long non-coding RNAs (lncRNAs) in cardiovascular physiology and the initiation and progression of cardiovascular disease (6)(7)(8). Early on in our study, we tested what genes were regulated by lncRNA260 by high throughput RNA and lncRNA chips screening and found that only the IL28RA gene was the only gene to be regulated by lncRNA260.…”
Section: Introductionmentioning
confidence: 92%